Proper management of suspicious actinic cheilitis - Soung Min Kim; Hoon Myoung; Mi Young Eo; Yun Ju Cho; Suk Keun Lee (Maxillofacial Plastic and Reconstructive Surgery, 2019)
Abstract Background Actinic cheilitis (AC) is a variant of actinic keratosis which is known to be a premalignant condition that could develop into squamous cell carcinoma (SCC). Epimyoepithelial carcinoma (EC) is a very rare salivary gland (SG) neoplasm that has classical biphasic histologic findings of small tubules and glandular lumina surrounded by clear myoepithelial cells. Case presentation We report a very rare case of AC occurring on the lower lip of a 70-year-old woman, which is developing to the EC later. Conclusions Diverse appearances of AC include edematous reddish in the acute stage and grey-whitish or dried hyperkeratotic wrinkled lesions in the chronic stage for several months or even years. Accurate treatment of AC in its initial stage could be recommended to avoid further malignant transformation; proper management of clinically suspicious AC is suggested.